Reinterpreting the Principle of Tabellionis Officium Fideliter Exercebo in Notarial Practice in the Digital Era of Society 5.0 - Ghadamfar Muflih Idroes (Genesis Law and Social Sciences, 2025)
The rise of Society 5.0 has driven significant technological transformations across various sectors, necessitating the adaptation of traditional legal principles to contemporary digital practices. This study examines the reinterpretation of the principle Tabellionis Officium Fideliter Exercebo in Indonesia’s notarial practice within the digital context of Society 5.0. Employing a normative juridical approach, the research explores how emerging digital technologies, including electronic signatures, teleconferencing, blockchain, and biometric authentication, can fulfill traditional legal requirements of authenticity, integrity, and physical presence in notarial acts. Although Indonesia’s current legal framework poses challenges to fully digital implementations, the analysis suggests that adaptive regulatory reforms could enable a hybrid notarial model. Such a model integrates traditional safeguards with technological innovations, enhancing legal certainty, accessibility, and inclusivity. Ultimately, this research advocates regulatory updates that maintain core notarial values while meeting modern societal expectations for efficient, trustworthy, and accessible legal services.